2022
DOI: 10.1093/wber/lhac005
|View full text |Cite|
|
Sign up to set email alerts
|

Technology, Skills, and Globalization: Explaining International Differences in Routine and Nonroutine Work Using Survey Data

Abstract: The shift from routine work to nonroutine cognitive work is a key feature of labor markets globally, but there is little evidence on the extent to which tasks differ among workers performing the same jobs in different countries. This paper constructs survey-based measures of routine task intensity (RTI) of jobs consistent with those based on the U.S. O*NET database for workers in 47 countries. It confirms substantial cross-country differences in the content of work within occupations. The extent to which worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Some evidence exists for the United States (see Autor, Levy and Murnane 2003) but this evidence is not conclusive. Furthermore, there exist substantial cross-country differences in the routineness of job tasks, both at the national level and within specific occupations (see Lewandowski, Park and Schotte 2020;Lewandowski et al 2022).…”
Section: Market Concentration Creates Entry Barriersmentioning
confidence: 99%
“…Some evidence exists for the United States (see Autor, Levy and Murnane 2003) but this evidence is not conclusive. Furthermore, there exist substantial cross-country differences in the routineness of job tasks, both at the national level and within specific occupations (see Lewandowski, Park and Schotte 2020;Lewandowski et al 2022).…”
Section: Market Concentration Creates Entry Barriersmentioning
confidence: 99%
“…GDP per capita in PPP, current international $, country averages for 2011-2016. Source: Lewandowski et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Less developed countries have a comparative advantage in performing routine tasks as they usually exhibit a lower skill supply than more developed countries (Grossman and Rossi-Hansberg, 2008). Indeed, Lewandowski et al (2022) found that the relationship between backward GVC participation and worker-level RTI is the strongest among workers in low-skilled occupations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations